A Comparative Thermal Performance Assessment of Various Solar Collectors for Domestic Water Heating. (16th June 2022) - Kalair, Ali Raza; Seyedmahmoudian, Mehdi; Saleem, Muhammad Shoaib; Abas, Naeem; Rauf, Shoaib; Stojcevski, Alex
Abstract : Growing population, depleting fossil fuels, economic expansions, and energy intensive life style demand are resulting in higher energy prices. We use energy as of heat and electricity, which can directly be obtained from sun using thermal collectors and solar cells. Solar thermal systems are gaining attention for water and space heating applications due to green aspects of solar energy. A solar thermal collector is a vital part of solar thermal energy system to absorb radiant energy from the sun. In this study, a solar water heating (SWH) system has been designed and simulated in the TRNSYS ® software using thermal and chemical properties of heat transfer fluids using REFPROP for dwellings located on ±31° latitudes (+31 Lahore in Pakistan and -31° Perth in Australia). We present an efficiency parametric optimization-based model for water and space heating. Simulation results for four types of solar thermal collectors are presented, and performance is analyzed on the basis of output temperature (T out ), solar fraction (f ), and collector efficiency (η ). This study evaluates the comparative performance of evacuated tube collector (ETC), flat-plate collector (FPC), compound parabolic concentrator (CPC), and thermosiphon-driven systems. Our findings conclude the evacuated glass tube collector achieves the highest solar fraction, i.e., 50% of demand coverage during August in Pakistan and February in Australia, with an overall average of 43% annually.